2022
DOI: 10.1136/jnis-2022-019815
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on one year functional outcomes after thrombectomy for young stroke patients

Abstract: BackgroundThe incidence of stroke in young patients (20–50 years old) has increased in recent decades. Unlike the use of good functional outcomes to evaluate prognosis, excellent functional outcomes are a better indicator of return to work among younger patients. The rate of return to work increases with time after stroke. This study investigated the short term (3 months) and long term (1 year) predictors of excellent functional outcomes in young patients after endovascular thrombectomy (EVT).MethodsWe include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In recent years, studies involving anterior and posterior stroke have shown that the proportion of patients with favorable outcomes after thrombectomy has ranged from 36% to 69.1%, and mortality has ranged from 12.7% to 26% at 1 year. 16,17 In our study, it is obvious that the long-term mortality and unfavorable outcome rates were high because of the inclusion of patients with posterior circulation infarction and the special focus on patients with FR.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, studies involving anterior and posterior stroke have shown that the proportion of patients with favorable outcomes after thrombectomy has ranged from 36% to 69.1%, and mortality has ranged from 12.7% to 26% at 1 year. 16,17 In our study, it is obvious that the long-term mortality and unfavorable outcome rates were high because of the inclusion of patients with posterior circulation infarction and the special focus on patients with FR.…”
Section: Discussionmentioning
confidence: 89%
“…Smoking can increase the permeability of the blood-brain barrier and disruption transport, causing brain edema after stroke and worsening the prognosis [ 19 ]. One study found that current or former smoking habits were independent negative predictors of 3- and 12-month functional outcomes in young patients after EVT [ 20 ]. It is worth noting that night shift work is more likely to lead to unhealthy lifestyles, which could also impact comorbidity and stroke outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke is a disease with a high incidence rate, high recurrence rate and high disability rate, affecting approximately 12 million patients worldwide every year, of which approximately 10% occur in individuals under 50 years old[ 7 , 8 ]. At present, the definition of youth stroke is not yet unified, and different studies have different definitions of its age limit.…”
Section: Discussionmentioning
confidence: 99%